2015
DOI: 10.1007/s11606-015-3238-1
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Platelet Count for Predicting Cirrhosis in Alcoholic Liver Disease: Model for Identifying Cirrhosis in a US Population

Abstract: BACKGROUND: Thrombocytopenia has been shown to be the single most useful laboratory investigation for identifying subclinical cirrhosis of varying etiologies. However, alcohol per se can result in thrombocytopenia, and hence it is unclear whether platelet count can identify cirrhosis in patients who are alcoholic. OBJECTIVES: To characterize the utility of clinical predictors, especially platelet count, for identifying the presence of cirrhosis in alcoholics. To develop a simple, objective model for identifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…12 In another study by Murali et al, they found significant correlation between Platelet and alcoholic liver cirrhosis with the median platelet count of less than 70x103cells/mm 3 was effective for ruling in alcoholic cirrhosis and a platelet count greater than 200x103 cells/mm 3 significantly decreased the likelihood of having cirrhosis. 13 A recent meta-analysis by Udell et al, identified thrombocytopenia as the single most important laboratory test for identifying cirrhosis of varying etiologies. 14 In present study mean platelet count for HbsAg cirrhosis patients was 98.5x103 cells/mm 3 and that of non-cirrhosis were 1.92x103 cells/mm 3 which was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…12 In another study by Murali et al, they found significant correlation between Platelet and alcoholic liver cirrhosis with the median platelet count of less than 70x103cells/mm 3 was effective for ruling in alcoholic cirrhosis and a platelet count greater than 200x103 cells/mm 3 significantly decreased the likelihood of having cirrhosis. 13 A recent meta-analysis by Udell et al, identified thrombocytopenia as the single most important laboratory test for identifying cirrhosis of varying etiologies. 14 In present study mean platelet count for HbsAg cirrhosis patients was 98.5x103 cells/mm 3 and that of non-cirrhosis were 1.92x103 cells/mm 3 which was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…SPI and LFI were found to be independent predictors of significant fibrosis, whereas GGT, SPI and LFI were independent predictors of cirrhosis. Numerous previous studies have demonstrated that platelet count, AST level, and AST/ALT ratio are important predictors of significant fibrosis or cirrhosis ( 33 , 34 ). However, in the present study, only the GGT laboratory parameter was independently associated with cirrhosis, which is in agreement with the results of previous studies ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopaenia, or low platelet count, occurs in up to 50% of patients with chronic liver disease (CLD). It is the most common haematological complication in patients with CLD . Thrombocytopaenia may be caused by multiple factors including reduced platelet production due to decreased production of thrombopoietin, splenic sequestration of platelets and increased platelet destruction .…”
Section: Introductionmentioning
confidence: 99%
“…It is the most common haematological complication in patients with CLD. [1][2][3][4][5][6][7] Thrombocytopaenia may be caused by multiple factors including reduced platelet production due to decreased production of thrombopoietin, splenic sequestration of platelets and increased platelet destruction. 8 Patients with cirrhosis and other decompensated CLD are at a higher risk for thrombocytopaenia; one review of management of thrombocytopaenia in this population suggests that up to 78% of patients with cirrhosis have thrombocytopaenia.…”
Section: Introductionmentioning
confidence: 99%